Constipation is Associated With Increased Hospital Utilization in Cystic Fibrosis: A National Inpatient Sample Analysis - Matt Pelton; Arvind Bussetty; Sarah Abdel-Meguid; Harrison Clement; Natale Mazzaferro; Tae Yang Park; Sugeet Jagpal; Christopher Vélez; Keerthana Kesavarapu (Gastro Hep Advances, 2025)
Background and Aims: Constipation in patients with cystic fibrosis (PwCF) is a debilitating symptom and, in its most severe forms, is associated with distal intestinal obstruction syndrome. This study aims to characterize the relationship between constipation during hospitalization and the symptoms, complications, and associated health-care costs of constipation in the National Inpatient Sample database. Methods: National Inpatient Sample was queried for discharges in the general population and PwCF from the years 2015–2019. Using International Classification of Diseases, Tenth Revision codes, hospitalized PwCF were matched with the general population on the Charlson comorbidity index, markers of hospitalization severity, and demographics. Subsequently, both were split into 2 cohorts: one with comorbid constipation and one without. Study outcomes were adjusted for gastrointestinal comorbidities, age, sex, and indication for admission. Results: Of 135,860 discharges, constipation was present in 14.0% in PwCF and 5.6% in the general population with average total charges of $104,270 and length of stay (LOS) of 8.8 days. Constipation was independently associated with increased LOS (1.22 days, standard error [SE] 0.21) and total charges ($14,280, SE $12,308) among PwCF, despite undergoing a similar number of endoscopic procedures (−0.02 SE 0.06). These findings were unchanged on subgroup analysis for sex and indication for hospitalization. Subgroup analysis showed a persistent association of higher costs with constipation in those with pancreatic insufficiency but not those with pancreatic sufficiency ($22,053 vs $493) despite a similar LOS. Conclusion: Comorbid constipation in hospitalized PwCF was independently associated with increased LOS and costs. The association worsened in those with pancreatic insufficiency.